KEMAMPUAN SOFT SKILL DAN KEMANDIRIAN BELAJAR MAHASISWA DALAM PERKULIAHAN ALJABAR ABSTRAK MELALUI MODEL PROBLEM BASED LEARNING (PBL) - Ilmadi Ilmadi; Elda Herlina (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The results of the study show that 80% of a person's success is supported by soft skills, so it is not wrong if these soft skills are the biggest supporting factor in determining student success in learning mathematics, in addition to having good soft skills, to support success in learning, independence study is also required. So there is a need for efforts to increase this ability through the application of learning models. In this study applying the Problem Based Learning (PBL) model as an alternative that is thought to be able to improve this ability. The aim of the study was to see an increase in soft skills and student learning independence, especially for students taking abstract algebra courses using the PBL model of the Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Pamulang University. The method in this research is quasi-experimental. The sample in this study were students taking abstract algebra courses consisting of 42 students of the Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Pamulang University. Data collection techniques using observation sheets, questionnaires, product assessment and test results. The indicators of soft skills seen in this study are honesty, verbal communication, participation in lectures and creativity. While indicators of learning independence are learning initiatives, diagnosing learning needs, setting learning goals, choosing and using resources, selecting and implementing learning strategies, independent learning, working with others and self-control. From the research results it is known that the soft skill ability indicators have increased starting from the first observation to the third observation, the average soft skill ability score for the honesty indicator is 3.59; verbal communication 3.70; participation 3.19 and creativity 3.17. Based on the criteria, each of these indicators is in the good category. While learning independence also increased before and after being given treatment, with an increase of 21.09; from the sig.(2-tailed) value of 0.000 which is less than the value of 0.05 so that it can be concluded that there is an influence of the PBL Model on learning independence